Climate Change Adaptation in Metro Manila: Community Risk Assessment and Power in Community Interventions - Porio, Emma E (Archīum Ateneo, 2014)
This chapter is based on a participatory community risk assessment (PCRA) of climate change-related effects (i.e., floods, increased number and intensity of typhoons and rains, storm surges, sea level rise) among marginal, riverine communities in Metro Manila, Philippines. Initiated by a university-based clinical sociology team, in partnership with women’s community based organizations (CBOs), this PCRA focused on assessing the flood impacts associated with tropical storms and typhoons from 2009 to 2012. The central goal of the collaboration was to produce a science-based assessment of climate change effects but anchored on participatory action research (PAR) principles. In this way, marginal groups will own and appreciate the data bases produced and their role in formulating more effective community-based risk reduction and management plans and programs. Clinical analysis and interventions aimed to promote community adaptation and resilience among vulnerable groups maximize the intersections of insider and outsider knowledge/expertise and institutional resources of marginal communities, academia, civil society and the state. This study documents how community-driven interventions facilitated adaptation strategies among the urban- poor communities and increased their resilience to climate change-related effects such as floods, typhoons and sea level rise (SLR). The community- based risk reduction and management plan formulated and implemented by the Tanza Women’s Association was anchored on the principle that community-driven initiatives create sustainable research-action networks and produce more collaborative, effective engagements and solutions among different sectors.